1973
DOI: 10.1104/pp.52.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production and Respiratory Behavior of the rin Tomato Mutant

Abstract: Little or no change in ethylene or C02 production occurred in rin tomato mutant fruits monitored for up to 120 days after harvest. Of the abnormally ripening tomatoes investigated, including "Never ripe" (Nr Y a h, Nr c 12 r), "Evergreen" (gf r) and "Green Flesh" (gf), only rin did not show a typical climacteric and ethylene rise.Fruits from F1 plants resulting from reciprocal crosses between rin and normal plants apeared to ripen normally, but when compared to normal fruit, their ripening was delayed as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
2

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 15 publications
4
72
0
2
Order By: Relevance
“…The increase was particularly obvious in the ripe Rutgers tomato, presumably due to the fruit tissue predisposition to sugar synthesis as shown above. The response of the rin, behaving like nonclimacteric fruit (8), is also significant; although in this tissue, the magnitude of the 14C recovery in the sugar fraction is equivalent to that of the green Rutgers fruit, the AA-treated rin mimicked a metabolic activity found in climacteric fruit. In ripening banana, starch is degraded to triose or hexose phosphates which diffuse from the amyloplast to the cytosol and are metabolically apportioned for glycolysis and in addition for gluconeogenesis (1).…”
Section: Resultsmentioning
confidence: 98%
“…The increase was particularly obvious in the ripe Rutgers tomato, presumably due to the fruit tissue predisposition to sugar synthesis as shown above. The response of the rin, behaving like nonclimacteric fruit (8), is also significant; although in this tissue, the magnitude of the 14C recovery in the sugar fraction is equivalent to that of the green Rutgers fruit, the AA-treated rin mimicked a metabolic activity found in climacteric fruit. In ripening banana, starch is degraded to triose or hexose phosphates which diffuse from the amyloplast to the cytosol and are metabolically apportioned for glycolysis and in addition for gluconeogenesis (1).…”
Section: Resultsmentioning
confidence: 98%
“…Nonripening Nr mutant fruit and unripe wild-type fruit treated with sufficient 1-MCP to stop normal ripening remain partially resistant to B. cinerea. Although they perceive ethylene, rin and nor mutant fruit fail to ripen (Herner and Sink, 1973;Tigchelaar et al, 1973;McGlasson et al, 1975a;Giovannoni, 2007b). Ethylene treatment of rin fruit induces the expression of some ripening-regulated genes (Lincoln and Fischer, 1988), and wounding rin and nor fruit induces ethylene production (Yokotani et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…No significant increase in ethylene evolution from MG and RR wild-type fruit inoculated with B. cinerea was observed at 1 dpi (Table I), although significant accumulation was observed at 3 dpi. Uninoculated rin and nor fruit produced less ethylene at all ripening stages compared with uninoculated wild-type fruit (Table I; Herner and Sink, 1973;McGlasson et al, 1975aMcGlasson et al, , 1975bThompson et al, 1999).…”
Section: Perception Of Ethylene and Fruit Susceptibilitymentioning
confidence: 99%
“…We have now shown that there is an active conversion of methionine to ethylene in wounded fruit tissue of both rin and nor, quantitatively similar to that in wounded normal fruit tissue. The production of ethylene in response to wounding contrasts with the lack of a natural respiratory climacteric and parallel increase in ethylene production during aging in whole rin fruit (3,5), and the occurrence of only a very small rise in ethylene production but no respiratory climacteric in intact aging whole nor fruit (2). These apparent differences in ethylene metabolism in aging leaves and freshly cut disks compared with intact aging whole fruits support Zobel's (11) suggestion of a possible divergence of mechanisms controlling ethylene synthesis in different tissues.…”
mentioning
confidence: 99%
“…Physiological studies with rin have shown that developing fruits contain low levels of ethylene similar to those in a normal strain and eventually turn yellow on the plant or following detachment (3,5 in this laboratory (2) has shown that immature fruits of nor also fail to exhibit a respiratory climacteric. Yellowing in nor fruits is associated with a small rise in ethylene production to a peak value about one-eighth of that in normal fruit.…”
mentioning
confidence: 99%